The Effects of Armed Conflicts on Treaties - Yocheva, Katerina (Yearbook of the Law Department, 2022)
What happens to treaties, concluded in peacetime, if and when an armed conflict between some or all of the parties thereto breaks out? The answer to such a question was and is one of the most disputed in international law. In the past there have been several attempts to regulate the related to this issue legal aspects on the international level, however the present study aims to make a review mainly of the rules, elaborated in 2011 by the UN International Law Commission. This set of 18 draft articles are of special importance in 2022 in the light of the outbreak of hostilities of February 2022 between the Russian Federation and Ukraine since there exist a good number of treaties to which those two states are parties as of 2022.